الاندماج في اقتصاد المعرفة: بین المتطلبات ومؤش ا رت القیاس - KNIDA, ZOULAYKHA (Milev Journal of Research and Studies, 2023)
the technical and scientific development has contributed to the intensive use of information and communication technology at the global level in the emergence of a new economic pattern, which is known as the knowledge economy, which depends on the productive structure of the non-material dimension of capital represented mainly in knowledge, which has become an important part in the creation of value added and the generation of wealth in the economy, and the accumulation is the motive of the main engine of economic growth. The shift toward knowledge economy requires a knowledge environment in which the production, acquisition, deployment, and employing knowledge efficiently in all economic activities, where information and communication technology occupies a central place, in addition to the interest in qualitative rather than quantitative learning, support for research and development, and the promotion of creativity and innovation, which constitute the basic ingredients for integration in the knowledge economy.